Influence of integrity, independence and competency on audit quality with auditor performance as an intervening variable in inspectorate of the Riau Island - Reza Chandra; Bambang Satriawan; Nola Puspita Dewi (LPPM STIE Krakatau, 2025)
Purpose: This study aims to determine the Effect of Integrity, Independence and Competence on Audit Quality with Auditor Performance as an Intervening Variable in Regional Inspectorates throughout the Riau Islands Province. Methodology/approach: A quantitative approach was applied, involving 137 auditor respondents. Data were collected via questionnaires and analyzed using SmartPLS 3. The study tested direct and indirect effects through path coefficient analysis, composite reliability, discriminant validity, and R-square evaluation. Results/findings: Integrity, independence, and competence each have significant positive effects on both auditor performance and audit quality. Auditor performance also significantly influences audit quality. Moreover, performance mediates the relationships between integrity, independence, competence, and audit quality. The model explains 71.4% of the variance in audit quality, indicating substantial predictive power. Conclusions: Integrity, independence, and competence boost audit quality directly and via performance, requiring strategies to strengthen these factors. Limitations: The study focuses on one province, limiting generalizability, and does not examine other relevant variables such as objectivity and discipline. Contribution: Provides empirical evidence on the mediating role of performance in improving public sector audit quality.